The framework of SENA’s comprehensive vocational training and interprofessional education in times of pandemics - Dueñas Garzón, Adriana Lucia
This writing emphasizes the reference framework of Comprehensive Vocational Training and Interprofessional Education in times of pandemic, prioritizing the ways in which teaching-learning processes are assumed and operationalized. It is also highlighted how some of its theoretical postulates can be combined and complemented, while contributing and favoring the organization, planning and orientation of new and better educational experiences. Although Comprehensive Vocational Training (FPI) located in the SENA institutional framework and Interprofessional Education (EIP) have their own purposes and centers of interest, they also have common aspects. Objective: To present in an overview the theoretical and conceptual bases that support the approaches of Comprehensive Vocational Training (FPI) located in the SENA institutional framework and Interprofessional Education (EIP) in health in times of Pandemic. Methodology: Type of study: Qualitative, descriptive, documentary study. Sample: Publications on Interprofessional Education April 2020 to April 2022; publications on Comprehensive Vocational Training from 1994 to 2019, compiled in a scientific support matrix for analysis. Conclusions: Interprofessional Education strengthens the teaching-learning-assessment process of Comprehensive Vocational Training based on collaborative work, promoting the acquisition of knowledge, development of abilities and skills within the framework of specific, transversal and interprofessional competencies in real learning contexts with the participation of interprofessional teams, which is reflected in significant learning and undoubtedly in an important synergy of the process of Comprehensive Vocational Training and Interprofessional Education.